Transforming Islamic Religious Education into Kitab Based Learning and Takhassus Programs - Mustaqim, Mustaqim; Efriyanti, Liza; Indra, Yossefli; Syahweli, Fahril (Ahlussunnah: Journal of Islamic Education, 2026)
This study aims to analyze the transformation of Islamic Religious Education subjects into kitab-based learning and the implementation of a takhassus (specialization) program in an Islamic boarding school. This transformation is driven by the need to strengthen students’ religious understanding through the integration of the formal curriculum with the traditional study of classical Islamic texts (turath). This study employs an exploratory sequential mixed methods design. Qualitative data were collected through interviews with the pesantren leader, head of the madrasah, and Islamic studies teachers, followed by quantitative data gathered through questionnaires administered to 30 students. Data were analyzed using descriptive qualitative analysis and descriptive statistics. The findings reveal that the transformation of IRE is implemented through the integration of the formal curriculum with classical Islamic texts in subjects such as Quran-Hadith, Aqidah-Akhlaq, Fiqh, and Arabic language. The takhassus program is conducted through in-depth study of classical texts using the sorogan and bandongan methods, supported by the use of modern instructional media. The program has a positive impact on improving students’ ability to read classical Arabic texts, enhancing their religious understanding, and increasing their learning motivation. This study concludes that the integration of kitab-based learning and the takhassus program strengthens the identity of Islamic boarding school education and enhances the overall quality of Islamic Religious Education in a holistic manner.